Proband‐Only Exome Sequencing for Intellectual Disability in Iran: Diagnostic Yield and Genetic Insights - Ghalamkari, Safoura; Mianesaz, Hamidreza; Chitsaz, Ahmad; Ghazavi, Mohammadreza; Salehi, Mansoor (American journal of medical genetics. Part A, 2025)
ABSTRACT Intellectual disability (ID) is a leading cause for referral to genetic services, with the most severe cases typically attributed to single genetic defects. This study aimed to evaluate the diagnostic yield of cost‐effective proband‐only exome sequencing for individuals diagnosed with ID within the Iranian population for the first time where a high rate of parental consanguinity exists. A total of 99 unrelated patients with ID were investigated by exome sequencing during 8 years. As a result, 43 pathogenic/likely pathogenic variants were identified in 40 patients, indicating a molecular diagnostic rate of 40.4% (40/99). The inclusion of five chromosomal copy number variations in the subsequent analysis increased the diagnostic rate of proband‐only exome sequencing to 45.4% (45/99). Additionally, parental testing revealed five de novo variants. This contributed to a total diagnostic rate of 50.5% (50/99). In our study, proband‐only exome sequencing achieved a remarkable diagnostic rate, identifying nearly half of the ID cases. This rate of diagnosis could be primarily attributed to prevalent consanguineous marriage in the Iranian population and the rare identification of de novo variants. With the ongoing advancements in neurogenetics, proband‐only exome sequencing demonstrates significant potential as a future cost‐effective diagnostic approach in Iran.